Changing climate and resource use efficiency in plants - Bhattacharya, Amitav (Elsevier Ltd. : Academic Press, 2019)
Changing Climate and Resource Use Efficiency in Plants reviews the efficiencies for resource use by crop plants under different climatic conditions. This book focuses on the challenges and potential remediation methods for a variety of resource factors. Chapters deal with the effects of different climatic conditions on agriculture, radiation use efficiency under various climatic conditions, the efficiency of water and its impact on harvest production under restricted soil moisture conditions, nitrogen and phosphorus use efficiency, nitrogen use efficiency in different environmental conditions under the influence of climate change, and various aspects of improving phosphorus use efficiency. The book provides guidance for researchers engaged in plant science studies, particularly Plant/Crop Physiology, Agronomy, Plant Breeding and Molecular Breeding. In addition, it provides valuable insights for policymakers, administrators, plant-based companies and agribusiness companies.